SISTEM ABSENSI MENGGUNAKAN SCAN QR CODE BERBASIS WEB - Khoirunnisya (Journal of Research and Publication Innovation, 2025)
Assessment is an important part of learning, there are 3 important points in the assessment of academic grades, presence, and behavior and attitudes. In attendance or attendance point is one aspect of assessment in determining the assessment of the increase or graduation of an individual in a student final report (report card). But from the aspect of one attendance there is often cheating so that the assessment of attendance does not go according to the principle of one aspect of discipline. Research Objectives To design and build a website application that makes it easy for the admin to carry out the attendance process in schools, and the results of this study are applications that utilize QR Code as the main component in helping the attendance process. The method applied to the development of the QR Code attendance system in developing this system is a prototype. But there are several additional methods such as interviews, observation and literature studies are used in obtaining some supporting data. The development of this web-based student attendance system is able to support and make it easier for admins to record student attendance data, avoid the cheating process when recording attendance and improve data security. Keywords: QR Code, Attendance, Prototype, Website